Forecasting the Catch Data of E.sinensis by Applying Continuous Time Markov Approach - Feng, Guangpeng; Li, Yanhua; Wu, Bin; Ma, Benhe; Hu, Huogen; Wang, Haihua (IOP conference series. Materials Science and Engineering, 2018)
The forecast model for catch data of E.sinensis was built by using continuous time Markov approach, combining with optimization method (0.618) based on of catch data of E.sinensis in Yangtze River estuary from 1970∼2012. And a forecast on the catch data of E.sinensis in 2013 was made in this paper. The result showed that the forecast was corresponded to the catch data accurately and provides a new method for the prediction of crab resources.